Attenuated allergic airway inflammation in Cd39 null mice. Issue 4 (1st March 2013) - Idzko, M.; K. Ayata, C.; Müller, T.; Dürk, T.; Grimm, M.; Baudiß, K.; Vieira, R. P.; Cicko, S.; Boehlke, C.; Zech, A.; Sorichter, S.; Pelletier, J.; et al.
Abstract Background Extracellular Adenosine‐5′‐Triphosphate (ATP) is known to accumulate in the lung, following allergen challenge, and contributes via activation of purinergic receptors on dendritic cells (DC), to the development of allergic airway inflammation (AAI). Extracellular ATP levels in the airways are normally tightly regulated by CD39. This ectonucleotidase is highly expressed by DC purified from skin (Langerhans cells) and bone marrow, and has been shown to modulate DC adaptive/haptenic immune responses. In this study, we have evaluated the impact of Cd39 deletion and associated perturbation of purinergic signaling in AAI. Methods Standard ovalbumin (OVA)–alum and house dust mite (HDM) bone marrow‐derived DC (BMDC)‐dependent models of AAI were used to study effects of Cd39. Migration assays, time lapse microscopy, and T‐cell priming assays were further used to determine functional relevance of Cd39 expression on BMDC in the setting of immune and Th2‐mediated responses in these models. Results Cd39 −/− mice exhibited marked increases in BALF ATP levels but paradoxically exhibited limited AAI in both OVA–alum and HDM models. These pathophysiological abnormalities were associated with decreased myeloid DC activation and chemotaxis toward ATP, and were linked to purinergic receptor desensitization responses. Further, Cd39−/− DCs exhibited limited capacity to both prime Th2 responses and form stable immune synaptic interactions with OVA‐transgenic naïve T cells. Conclusions Cd39‐deficient DCs exhibit limited capacity to induce Th2 immunity in a DC‐driven model of AAI in vivo. Our data demonstrate a role of CD39 and perturbed purinergic signaling in models of AAI.